Mohammad Roem's Skills As A Negotiator In The Roem-Royen Negotiations - Dewi, Rifqoti Ulya (JURNAL HISTORICA, 2024)
Mohammad Roem is a diplomatic figure who was involved in the Roem-Royen Negotiations as a figure in the Indonesian delegation. This study aims to find out the figure of Mohammad Roem and his skills in negotiating with the Dutch in the Roem-Royen Negotiations. The method used in this study is the historical research method. The Roem-Royen Negotiations were negotiations between Indonesia and the Netherlands which began on April 14 1949 and were signed on May 7 1949. These negotiations were held at the Des Indes Hotel, Jakarta. This negotiation is also an example of how diplomacy was able to resolve the conflict between two countries, namely Indonesia and the Netherlands, thereby creating bilateral relations between the two countries which had been in conflict. His involvement as a negotiator and Indonesian delegate in these negotiations is not surprising because Mohammad Roem is often involved in international negotiation s, which has made his name increasingly famous. His expertise as a negotiator in the Roem-Royen Negotiations can be used as evidence that the statement of willingness to make peace that was made was not just any statement but was for the sake of realizing peace between the two countries, both Indonesia and the Netherlands. The existence of these negotiations was ultimately able to open up opportunities to hold a Round Table Conference (KMB) in Netherlands.